1991
DOI: 10.1111/j.1439-0523.1991.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Regeneration from Anther Culture of Sunflower (Helianthus annuus) and Some Interspecific Hybrids as Affected by Genotype and Culture Procedure

Abstract: Anther culture has been demonstrated to be an applicable technique for the development of doubled haploid, i. e. homozygous lines of many crop species. In some species, androgenetic doubled haploids have already been shown to be a useful tool for breeding. However, anther culture results in sunflower have been rather unsatisfactory up to now.As in other species, anther culture response of sunflower {Helianthus sp.) is strongly affected by physical, nutritional, physiological and genetical factors. By testing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
(7 reference statements)
1
25
0
Order By: Relevance
“…The bud stage found to yield the highest percentage of anther calluses, 3.5 mm in diameter, corresponded to the early uninucleate stage of microsporogenesis in most of the developing florets. The early-to-mid uninucleate stage is reported as being an appropriate time for harvesting anthers of cereals (Dunwell, 1985), Brassica (Wenzel & Foroughi-Wehr, 1984) and the Asteraceous species safflower ( Carthamus tinctorius) (Prasad et al, 1990) and sunflower (Helianthus annuus) (Bohorova et al, 1985;Gurel et al, 1991;Thengane et al, 1994). Greater than 50% of floret isolations callused when harvested from capitula with diameters of between 2.9 and 3.8 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The bud stage found to yield the highest percentage of anther calluses, 3.5 mm in diameter, corresponded to the early uninucleate stage of microsporogenesis in most of the developing florets. The early-to-mid uninucleate stage is reported as being an appropriate time for harvesting anthers of cereals (Dunwell, 1985), Brassica (Wenzel & Foroughi-Wehr, 1984) and the Asteraceous species safflower ( Carthamus tinctorius) (Prasad et al, 1990) and sunflower (Helianthus annuus) (Bohorova et al, 1985;Gurel et al, 1991;Thengane et al, 1994). Greater than 50% of floret isolations callused when harvested from capitula with diameters of between 2.9 and 3.8 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Anther culture has been reported for crosses involving cultivated sunflower and wild Helianthus species and the regeneration frequencies for hybrids involving the hexaploid species was high as compared to those from crosses with diploid perennials (Jonard and Mezzarobba 1990). Gurel et al (1991) and Nurhidayah et al (1996) demonstrated the high regeneration potential of the anthers of interspecific hybrids involving hexaploid species. The regeneration frequency achieved in this study is high as compared to the other studies.…”
Section: Discussionmentioning
confidence: 97%
“…It requires a large number of anther culture plantlets to be analyzed for both ploidy status and reaction to A. helianthi and highly fertile diploid plantlets with high degree of resistance to the target pathogen could be selected for further advancement of generation. In vitro studies on H. annuus · H. tuberosus including anther culture were reported earlier but were mostly confined to assess the morphogenic competence of various tissues and utilization of these products in transfer of desirable traits into sunflower has not been presented (Witrzens et al 1988;Jonard and Mezzarobba 1990;Gurel et al 1991;Pugliesi et al 1993;Fambrini et al 1996;Nurhidayah et al 1996). But the present investigation revealed information about the high regeneration potential of the interspecific hybrids involving hexaploid Helianthus species which are important sources of disease and insect resistance and utility of anther culture plants of these hybrids in introgression of resistance to A. helianthi in to cultivated sunflower which is a major production constraint of sunflower crop in the semi-arid tropics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We hope that publication of this list will help in further application of DH technology in crop improvement and basic research. Shamina, 1986, 1993;Contolini and Menzel, 1987;Stelly et al, 1988;Bajaj and Gill, 1997;Khushwinder et al, 1998Guizotia abyssinica a Makhmudov, 1978Chaudhari, 1979;Mahill et al, 1984;Sarvesh et al, 1993;Adda et al, 1994 Mezzarobba and Jonard, 1986;Hongyuan et irr al., 1986;Gelebart and San, 1987;Gurel et al, 1991;Thengane et al, 1994;Coumans and Zhong, 1995;Zhong et al, 1995;Nurhidayah et al, 1996;Badigannavar and Kuruvinashetti, 1996;Todorova et al, 1997;Friedt et al, 1997;Saji and Sujatha, 1998;Todorova and Ivanov, 1999 Dryanovska, 1966;Prakash and Giles, 1986;Miki-Hirosige et al, 1988;Qu et al, 1988;Han et al, 1997Han et al, , 1999 Rose et al, 1987a;Pasakinskiene et al, 1997;Humphreys et al, 1998;Zare et al, 1999Rose et al, 1987a,b Ormerod and Caligari, 1994Sator et al, 1982Fan et al, 1982Gulshan et al, 1981Zagorska et al, ...…”
mentioning
confidence: 97%